2012
DOI: 10.1007/s10596-012-9286-2
|View full text |Cite
|
Sign up to set email alerts
|

Global sensitivity analysis in an ocean general circulation model: a sparse spectral projection approach

Abstract: Polynomial chaos (PC) expansions are used to propagate parametric uncertainties in ocean global circulation model. The computations focus on short-time, high-resolution simulations of the Gulf of Mexico, using the hybrid coordinate ocean model, with wind stresses corresponding to hurricane Ivan. A sparse quadrature approach is used to determine the PC coefficients which provides a detailed representation of the stochastic model response. The quality of the PC representation is first examined through a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 48 publications
2
93
0
Order By: Relevance
“…Suitable metrics are provided by the so-called Sobol sensitivity (global) indices. [56][57][58][59][60][61] In the analysis below, we rely on the first-order indices and total sensitivity indices associated with the first and second components of the germ. The first-order sensitivity indices, S 1 and S 2 , essentially quantify the direct contribution of n 1 (D 0 ) and n 2 (E a ) to the variance of the QoI, Q, whereas the total sensitivity indices, T 1 and T 2 , combine the direct contribution with that arising from mixed terms.…”
Section: Pc Surrogatementioning
confidence: 99%
“…Suitable metrics are provided by the so-called Sobol sensitivity (global) indices. [56][57][58][59][60][61] In the analysis below, we rely on the first-order indices and total sensitivity indices associated with the first and second components of the germ. The first-order sensitivity indices, S 1 and S 2 , essentially quantify the direct contribution of n 1 (D 0 ) and n 2 (E a ) to the variance of the QoI, Q, whereas the total sensitivity indices, T 1 and T 2 , combine the direct contribution with that arising from mixed terms.…”
Section: Pc Surrogatementioning
confidence: 99%
“…The Bayesian Inference analysis revealed a C max of about 2.3 × 10 −3 , that occurs upward of V max = 34 m/s, and that the ITOP data was D inconclusive with regard to the slope m beyond saturation (figures 3 and 4). This work has been summarized in a manuscript that is currently under review (Sraj et al (2012)). …”
Section: Work Completedmentioning
confidence: 99%
“…This calculation is the most CPU-intensive portion of the forward UQ problem, and directly impacts the accuracy of the resulting PC expansions. In our previous work (Alexanderian et al (2012)) an ensemble of 385 members were required to explore a four-dimensional parameter space where each variable was expanded in 5th-order PC expansion. Subsequent analysis, however, revealed that the quantity of interest (surface temperature) was insensitive to 3 out of the 4 parameters, that the response for 2 of the four parameters is almost linear, and that 7-th order polynomials would be preferable in one direction.…”
Section: Work Completedmentioning
confidence: 99%
“…[30][31][32][33] The PC-based model provides a complete probabilistic representation of the outputs in terms of the random inputs. PC may suffer from "the curse of dimensionality" 34 which limits the application of PC to only a moderate number of stochastic parameters for surrogate model construction. Nonetheless, PC methods have become one of the standard approaches for solving stochastic problems, to propagate and quantify uncertainties in various disciplines including physical, [35][36][37] chemical, and geophysical systems.…”
Section: Introductionmentioning
confidence: 99%